The brightest way (Confluenţe Bibliologice, 2014)
We need to know that each person is accompanied on the path of life by God and the Blessed Virgin Mary, and remember that the more beautiful all the facts that come to weaken the wicked, the latter respond with double, triple kindness, tenfold and so on, until you repay him definitely with malice. Kindness always makes us superior to the wicked.
Keywords: religious education